Tempeh Nuggets as an Additional Feeding Intervention to Prevent Stunting in Padang Village, Lumajang: Nugget Tempe sebagai Intervensi Pemberian Makanan Tambahan Pencegahan Stunting di Desa Padang Lumajang - Beti Werdiningsih; Musviro; Anita Sulistyawati; Aulia Ulin Tarisa (Journal of Community Empowerment for Multidisciplinary (JCEMTY), 2023)
Stunting is a condition when toddlers have a height or length disproportionate to the height of their age. Supplementary feeding is an intervention program for under-fives who suffer from malnutrition with the aim of improving nutritional status and meeting the nutritional needs of children. One of the interventions that can be done to prevent stunting is the provision of additional foods that are high in protein. The goal of this community service is to increase the knowledge of mothers of toddlers related to stunting and stunting prevention interventions. This community service method is through interactive health counseling, namely lectures and questions and answers to 21 mothers of toddlers, which was held on July 19, 2023, at the Padang Village Hall, Padang District. The results of this community service activity went well and smoothly. This is evidenced by the activation of the participants in question, and the average knowledge of the participants increased from education 6.73 to 7.60. Tempe is a processed fermented soybean Rhizopus sp mold, the fermentation process will change the physical and chemical form of soybeans into tempeh products that are highly nutritious and can be used as functional foods. Tempe with its protein, carbohydrate, fat, fiber, vitamins, and minerals content can be easily digested and is suitable for all age groups ranging from infants to the elderly. Tempe nuggets are processed products in frozen form that are ready to be cooked. Tempe nuggets can be one of the innovations of high-protein supplementary foods to prevent stunting.